Effects of fatigue on ground reactions forces-related variables: A systematic review in long-distance runners - Silva, M.; Afonso, J.; Ramirez-Campillo, R.; Fernandes, R. J.; Conceição, F. (European Journal of Human Movement, 2024)
Ground reaction forces (GRF) are a critical element acting on the joints of the lower limbs and the presence of fatigue may potentially modify running biomechanics. This systematic review aimed to assess and synthesize the current evidence on the effects of fatigue on GRF-related variables in long-distance runners. Following the PRISMA 2020 guidelines, four databases were consulted in September 2024 followed by a search of reference lists and expert suggestions. Eligibility criteria included healthy competitive or recreational long-distance runners, performing before and after an exercise-based fatigue-inducing protocol, and assessing GRF-related variables on a treadmill or overground using a force plate (the gold standard for kinetic performance analysis). 14 studies (345 participants, 193 females) were included. The studies investigated 27 different variables (with loading rate, active peak force and peak ankle plantarflexor). Most studies exhibited no effect of fatigue on GRF-related variables and there was considerable heterogeneity between studies (e.g., populations, interventions and testing). Risk of bias in the studies was moderate to high and certainty of evidence was judged as very low. Based on available data, there is no significant effect of fatigue on GRF during running, being uncertain to what extent they affect performance overall. Future research should focus on the ecological validity of the study, replicating the experiments during outdoor running.